The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1051/0004-6361/201117580
|View full text |Cite
|
Sign up to set email alerts
|

Solar low-lying cool loops and their contribution to the transition region EUV output

Abstract: Aims. We aim to investigate the increase of the differential emission measure (DEM) towards the chromosphere. In the past 30 years, small and cool magnetic loops (height < ∼ 8 Mm, T < ∼ 10 5 K) have been proposed as an explanation for this effect. Methods. We present hydrodynamic simulations of low-lying cool loops in which we studied the loops' conditions of existence and stability, and their contribution to the transition region EUV output. Results. We find that stable, quasi-static cool loops (with velociti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In terms of modelling, it would be interesting to see what onedimensional loop models would predict for very short loops that are heated to 1.5 MK or more, if that is possible. The models by Sasso et al (2012) produce transition region loops with temperatures well below 1 MK only. If, in those models, the energy input is increased, the loops might reach higher temperatures, and it would be interesting to see if they turn out to be stable or highly intermittent.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of modelling, it would be interesting to see what onedimensional loop models would predict for very short loops that are heated to 1.5 MK or more, if that is possible. The models by Sasso et al (2012) produce transition region loops with temperatures well below 1 MK only. If, in those models, the energy input is increased, the loops might reach higher temperatures, and it would be interesting to see if they turn out to be stable or highly intermittent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that, although heating by single pulses might explain the majority of DEMs derived in the literature (Bradshaw et al , 2010 ) and that trains of nanoflares might explain practically all of them (Reep et al , 2013 ), the uncertainties in the data analysis and DEM reconstruction are too large reach conclusive answers. Radiative losses are important to the existence of small and cool loops (height ≤ 8 Mm, T ≤ 10 5 K) that determine the cool side of the emission measure distribution (Sasso et al , 2012 ).…”
Section: Loop Physics and Modelingmentioning
confidence: 99%
“…Short loops have been studied theoretically (e.g. Müller et al 2003;Sasso et al 2012), indicating that such short hot structures are reasonable, even though these short model loops show peak temperatures of well below 1 MK. Klimchuk et al (1987) found that hot short loops with heights below 1000 km are thermally unstable and evolve into cool loops with temperatures around 10 5 K. This would apply to the miniature loops proposed here, which would not be stable, anyway, because they can be expected to be disturbed rapidly by the convective motions of the granulation.…”
Section: Miniature Coronal Loops In Plage Regionmentioning
confidence: 99%